2015
DOI: 10.4253/wjge.v7.i1.73
|View full text |Cite
|
Sign up to set email alerts
|

Russell body duodenitis with immunoglobulin kappa light chain restriction

Abstract: Russell bodies are eosinophilic intracytoplasmic globules which are likely the result of disturbed secretion of immunoglobulins that accumulate within the plasma cell. Russell body collections have been identified within the stomach, known as Russell body gastritis. Similar lesions within the duodenum are referred to as Russell body duodenitis, which is rare. Several Russell body gastritis case reports are associated with Helicobacter pylori. However, the etiology of Russell body duodenitis remains unclear. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Chen et al [20] 2013 1 59 F Duodenum Yes Polyclonal Diabetes, Hypertension COPD NS 5 zhang et al [9] 2014 1 76 M Duodenum Yes Monoclonal (λ) CP NS 6 Munday et al [21] 2015…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [20] 2013 1 59 F Duodenum Yes Polyclonal Diabetes, Hypertension COPD NS 5 zhang et al [9] 2014 1 76 M Duodenum Yes Monoclonal (λ) CP NS 6 Munday et al [21] 2015…”
Section: Discussionmentioning
confidence: 99%
“…Since then, approximately 20 cases of RBG have been reported. RBD is a rare disease, which Savage et al [ 4 ] first reported in a patient positive for HIV; only five cases have since been reported [ 5 - 8 ]. The differential diagnoses include plasmacytoma, mucosa-associated lymphoid tissue lymphoma, and signet ring cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…However, only one of the five previously reported cases of RBD was positive for H. pylori . The other background diseases were HIV infection in one [ 4 ], Crohn disease in one [ 5 ], retroperitoneal metastasis of ureteral cancer in one [ 6 ], and adenocarcinoma of the ascending colon in one case [ 8 ]. Although the development of Russell bodies is assumed to be associated with chronic inflammation, microorganisms, and immunodeficiency, the causes of their development remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…1-3 ▸ It is generally considered a benign entity, but given its epidemiology and the fact that Mott cells are associated with certain haematological malignancies such as multiple myeloma, plasmacytoma and mucosaassociated lymphoid tissue (MALT) lymphoma, there is still some doubts concerning its true clinical significance, particularly regarding the risk for gastric cancer development and so, follow-up is mandatory. [1][2][3] …”
Section: Descriptionmentioning
confidence: 99%